2018 Interstices Under Construction Symposium: Presence BROCHURE - Gatley, Julia; Barrie, Andrew; Jenner, Ross; Douglas, Andrew; Hedges, Susan (Interstices: Journal of Architecture and Related Arts, 1970)
***